Separation and Determination of charged drugs in aqueous and biological media using capillary zone electrophoresis coupled to different detectors - درويش كنده (Latakia University Journal -Medical Sciences Series, 2024)
In order to determine the pharmacokinetics and pharmacodynamics profiles of drugs after administration by varying routes, capillary electrophoresis coupled to different detectors, as a simple alternative analytical method, was developed to separate and determine both the anticholinergic (Glycopyrronium Bromide; the cationic substance) and the modified gamma cyclodextrin (Sugammadex; the anionic substance) in water and in human biological media; urine and plasma. All the results showed that there is an excellent linear relationship between the peak areas and the corresponding concentrations, and that is confirmed by the value of the correlation coefficient (R2 > 0.99). The detection for glycopyrronium bromide was in micrograms per milliliter sensitivity limit (using ultraviolet detector) after a short time of injection. The samples were easily pre-treated; urine samples were diluted with water and plasma ones were treated with acetonitrile. The method showed good reproducibility with RSD < 0.28% for migration time and < 0.92% for peak area at different media. Since sugammadex is a non-active ultraviolet substance, there is no possibility to be directly detected using an analytical instrument coupled to ultraviolet detector. In this study, it was determined easily and rapidly using contactless conductivity detector in water and human urine samples.